Back to human how great leaders create connection in the age of isolation - Dan Schawbel (New York, NY Da Capo Lifelong, 2018)
"Back to Human explains how a more socially connected workforce creates greater fulfillment, productivity, and engagement while preventing burnout and turnover"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Business communication